Growth Hormone Deficiency in Fanconis Anemia - Roy, Mahua (Springer-Verlag, 2011)
Two cases of Fanconis anemia (FA) are reported here. Case 1 presented with hypoplastic anemia and skeletal abnormality. Case 2, his older brother had stunted growth, investigations detected growth hormone deficiency and mild hematological derangement without other endocrine abnormality. FA was confirmed by positive chromosomal breakages studies in both cases.